Pleomorphic xanthoastrocytoma. A case report - Mucha-Małecka, Anna; Urbański, Jacek; Gliński, Bogdan (Contemporary Oncology/Współczesna Onkologia, 2005)
Pleomorphic xanthoastrocytoma (PXA) is a rare variant of cerebral glioma. It is characterized by quite good prognosis with 10-year relapse-free survival and overall survival of 61% and 70%, respectively. It occurs primarily in young adults and looks like a superficial cyst located mainly in the temporal and occipital lobe. Histologic examination usually reveals atypical cells, increased mitotic index and presence of necrosis (increased mitotic index and necrosis are recognized prognostic factors). The basic treatment modality for PXA is surgical resection the extent of which is the major prognostic factor. The role of adjuvant radiotherapy and chemotherapy is not well established. Radiotherapy with total doses of 30-60 Gy is recommended in patients after subtotal resections and in those who have a malignant variant of PXA. Chemotherapy is not used as a routine procedure. The paper describes a case of a 28-year-old woman with a history of escalating headache, nausea, disturbances of consciousness. Computed tomography (CT) of the head revealed big, cyst-like tumor involving right frontal, temporal and occipital lobes. The patient underwent subtotal resection of the tumor. Histologic examination revealed PXA with focal anaplasia WHO II/III. Because of unfavorable prognostic factors (subtotal resection, features of anaplasia) the patient received adjuvant radiotherapy. The total dose of 50.4 Gy in 30 fractions (two fractions a day) was given to the surgical bed and residual tumor with appropriate margins. CT performed after the treatment did not reveal any recurrence in the surgical bed. Up to now the patient remains in a good general condition and without deterioration of the neurological status.